Report of the Inter Ministerial Group Customs Procedures and Functioning of Container Freight Stations and Ports - Planning Commission (Planning Commission, 2004)
This Report is aimed at streamlining the customs procedures and the functioning of Container Freight Stations (CFS) at India’s major seaports with a view to reducing the dwell time of cargo and the associated costs. Maritime trade is becoming an increasingly important dimension of India’s growing economy. In fiscal 2005-06, Indian exports crossed $101 billion representing an annual growth of 25%. Similarly, imports crossed $140 billion in the same year. Though some improvements have been witnessed in the recent past, numerous bottlenecks continue to persist in the chain of maritime trade. As a result, the turnaround time for ships at Indian ports is significantly longer compared to other major ports in the Asian region. This compromises the competitiveness of Indian industry and trade potential and, therefore, needs to be addressed on priority.
Planning Commission Government of India
Planning Commission Government of India